HUBUNGAN DUKUNGAN KELUARGA DENGAN TINGKAT KECEMASAN PADA REMAJA DENGAN BULLYING DI SMA NEGERI 7 JAKARTA - Noer Aeni Zam Zam Mia, (2020)
Adolescence is a period of transition from children to adults in which physical or biological, cognitive and psychosocial changes occur. Changes experienced during adolescence will cause various problems both inside and outside themselves, causing stressors. One of the stressors that threatens adolescent psychology is bullying. Bullying can cause one of the psychological problems of adolescents, namely anxiety. Social support especially from families is important for adolescent mental health in undergoing a period of transition. This study aims to determine the relationship of family support with anxiety levels in adolescents with bullying at 7 Senior High School, Jakarta. This research is a quantitative research with Cross Sectional design. The sampling technique is by simple random sampling. The number of research samples were 148 respondents. Data analysis in this study used the Pearson Correlation Test and the T-Independent test. The results of this study found p value (0,000) <0.05, which means that there is a relationship between family support with anxiety levels in adolescents with bullying in 7 Senior High School Jakarta. Therefore, it is expected that nurses can provide education related to anxiety experienced by adolescents with bullying, schools are expected to provide counseling guidance to students who are victims and perpetrators of bullying, and for families, especially parents, are expected to be able to increase support for their teenage child.